PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING STUDI PERSEPSI DAN HARAPAN DOSEN DAN MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Tika Amelia (Universitas Negeri Padang, 2018)
Abstract: This study aims to explain how the use of e-learning based learning media in the Department of Economic Education FE UNP.Yang seen through the five indicators of the use of e-learning learning media that is 1) Self learning materials 2) E-moderating 3) Time and place flexibility 4) Instructional design 5) Evaluation. This type of research belongs to a comparative descriptive research using primary data as research data. The sample of this study amounted to 83 students and lecturers. Sampling with Proportional random sampling. Data analysis techniques used are descriptive analysis and analysis using Cartesian diagram. The result of analysis shows that the five indicators of the use of e-learning based learning media is quite good in terms of perceptions and expectations of lecturers and students, the results of analysis with the Importance performance matrix and Cartesian diagram shows the lecturer and students perceive all the indicators lower than expected and need to be improved. The results showed that there is a significant difference between the perception and expectation of lecturers and students toward the use of e-learning based learning media, which means the use of e-learning based learning media has not been implemented optimally. Therefore it is suggested to the teaching staff to increase the intensity of the use of e-learning based learning media in learning especially on evaluation and intruksional desigKeyword: E-learning,perception, expectation.